Gastrointestinal Manifestations of COVID-19 Infection: Clinicopathologic Findings in Intestinal Resections Performed at Single Institution - Burkett, Alison E.; Sher, Sophia B.; Patel, Chirag R.; Ildin-Eltoum, Isam; Dhall, Deepti; Margaroli, Camilla; Peter, Shajan; Lee, Goo; Bajpai, Prachi; Benson, Paul V.; Manne, Upender; Al Diffalha, Sameer (Frontiers in Medicine, 2022)
It is now known that COVID-19 not only involves the lungs, but other organs as well including the gastrointestinal tract. Although clinic-pathological features are well-described in lungs, the histopathologic features of gastrointestinal involvement in resection specimens are not well characterized. Herein, we describe in detail the clinicopathologic features of intestinal resection specimens in four patients with COVID-19 infection. COVID-19 viral particles by in situ hybridization and immunofluorescence studies are also demonstrated. All four patients were males, aged 28-46 years, with comorbidities. They initially presented with a severe form of pulmonary COVID-19 and showed gastrointestinal symptoms, requiring surgical intervention. Histopathologic examination of resected GI specimens, mostly right colectomies, revealed a spectrum of disease, from superficial mucosal ischemic colitis to frank transmural ischemic colitis and associated changes consistent with pneumatosis cystoides intestinalis. Three patients were African American (75%), and one was Caucasian (25%). In conclusion, COVID-19 infection, directly or indirectly, can cause ischemic gastrointestinal complications, with predilection for the right colon.